The problem of technical teacher training in modern conditions - A. P. Usoltsev; B. E. Starichenko; E. S. Koscheeva (Образование и наука)
Introduction. The article deals with the problem of selecting the content of the training of future teachers of general technical disciplines. It is proved that in conditions of multi-vector technical development, and turbulence associated with the transition to a multi-polar world order, the content of this training should change rapidly. Not only the given invariant of this content is important, but also the methodology of its formation.Aim. The present research aims to formulate the problem of developing the content for technical teacher training.Methodology and research methods. The developed methodology foundations for the selection of optimal content for technical teacher training are based on activity, competence-based, transfessional and transprofessional approaches. The empirical base was obtained using a distance questionnaire to technical teachers from 26 universities. The following theoretical methods were applied: retrospective analysis of the working conditions of teachers of technical disciplines; analysis of scientific and methodological literature on the problem of combining subject-professional and pedagogical training of a technical teacher; analysis of disciplines from professional training programmes in the Russian universities.Results. The analysis of vocational training programmes of technical and pedagogical universities made it possible to compare them with each other and to correlate the disciplines of the general professional block and elective courses to the main current directions of the Russian technical development in the current conditions. This made it possible to identify the content of the professional activity of the future technical teacher, as well as to indicate the possibilities for changing this content both in technical and pedagogical universities in order to more accurately match it with the existing tasks of technical development of the state. As a result of a retrospective analysis, a historically formed “portrait” of a technical was described. The following problems were indicated: “physical and technical snobbery” as unwillingness to enter the humanities and pedagogical field of professional activity from the physical and technical content of their subject; a low level of methodological knowledge and skills; lack of erudition in technical fields among young teachers; low professional self-esteem.Scientific novelty consists in the fact that for the first time the analysis of the disciplines of the general professional module and elective courses of technical and pedagogical universities of Russia revealed their correlation with the main directions of the development of science, technology and engineering.Practical significance. The conducted research allowed the authors to raise questions about the selection of the content of technical teacher training. This should help in the formulation of the principles of content selection to develop its methodology.